Ekstrak Stevia dan Lada Putih Bangka sebagai Antibakteri pada Pembuatan Sabun Padat - Miftah, Muhammad; Harismah, Kun (Prosiding University Research Colloquium, 2020)
Soap is a product that is very useful as a cleaning tool to remove dirt. Soap also functions in cleaning bacteria and fungi that are on the body. There are many variations on the soap that has been used by the community, but antibacterial soap with natural ingredients is still underutilized. One of the natural ingredients that can be used as antibacterial in soap are stevia leaves and white pepper. The content in stevia leaves is stevioside which works as an enzyme, while white pepper extract contains alkaloids and essential oils found in pepper can also be used as antibacterial. The purpose of this study was to prove that the extract from stevia leaves and white pepper can inhibit the antibacterial effectiveness of solid soap. Tests were carried out on Staphylococcus aureus bacteria. The best results from the antibacterial effectiveness test were obtained in 3 mL stevia extract and 1.5 mL white pepper extract, which was 19.38 mm.